2016
DOI: 10.1038/nature17640
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation on N6-adenine in mammalian embryonic stem cells

Abstract: It has been widely accepted that 5-methylcytosine is the only form of DNA methylation in mammalian genomes. Here we identify N6-methyladenine as another form of DNA modification in mouse embryonic stem cells. Alkbh1 encodes a demethylase for N6-methyladenine. An increase of N6-methyladenine levels in Alkbh1-deficient cells leads to transcriptional silencing. N6-methyladenine deposition is inversely correlated with the evolutionary age of LINE-1 transposons; its deposition is strongly enriched at young (<1.5 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

33
655
5
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 564 publications
(700 citation statements)
references
References 41 publications
33
655
5
7
Order By: Relevance
“…1a). In Dikarya, we observed 6mA levels broadly similar to those previously reported in model eukaryotic genomes [1][2][3][4] , ranging from 0.048% (Leucosporidiella creatinivora; Pucciniomycotina) to 0.21% (Protomyces lactucaedebilis; Taphrinomycotina). In contrast, we found high levels of 6mA in some early-diverging fungi, where up to 2.8% (Hesseltinella vesiculosa; Mucoromycotina) of all adenines were methylated (Fig.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…1a). In Dikarya, we observed 6mA levels broadly similar to those previously reported in model eukaryotic genomes [1][2][3][4] , ranging from 0.048% (Leucosporidiella creatinivora; Pucciniomycotina) to 0.21% (Protomyces lactucaedebilis; Taphrinomycotina). In contrast, we found high levels of 6mA in some early-diverging fungi, where up to 2.8% (Hesseltinella vesiculosa; Mucoromycotina) of all adenines were methylated (Fig.…”
supporting
confidence: 70%
“…However, genomic 6mA has recently been demonstrated to play crucial roles in both gene and transposon regulation, where it either (i) suppresses expression of transposable elements in animals during development [2][3][4] or (ii) is associated with promoters of actively expressed genes and is involved in nucleosome positioning in algae 1 . These studies demonstrate that while 6mA is present in eukaryotes, it may serve distinct genomic functions across diverse phylogenetic groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the year, Xiao's group and another led by John Gurdon of the Gurdon Institute in Cambridge, UK, showed that 6 mA can be found at exceedingly low levels in a variety of vertebrate species including mouse and human 13,14 . When Xiao's group looked at the distribution of the mark in mouse embryonic stem cells, the team found the strongest peaks on the X chromosome.…”
Section: The A's Have Itmentioning
confidence: 99%
“…Here, the mark seemed to be involved in silencing gene expression. The researchers also identified an enzyme that seems to be a 6 mA eraser 14 .…”
Section: The A's Have Itmentioning
confidence: 99%